The (normal) rate of capacity utilization at the firm level - Michalis Nikiforos (Levy Economics Institute of Bard College, 2012)
This paper examines the endogeneity (or lack thereof) of the rate of capacity utilization in the long run at the firm level. We provide economic justification for the adjustment of the desired rate of utilization toward the actual rate on behalf of a cost-minimizing firm after examining the factors that determine the utilization of resources. The cost-minimizing firm has an incentive to increase the utilization of its capital if the rate of the returns to scale decreases as its production increases. The theory of economies of scale provides justification for this kind of behavior. In this manner, the desired rate of utilization becomes endogenous.
Keywords: B20; B50; D21; E11; E12; E22; E25; 330; Kaleckian; Long Run; Economies of Scale; Utilization